Two-step production of anti-inflammatory soluble factor by Lactobacillus reuteri CRL 1098. - Milagros Griet; Graciela Font de Valdez; Carla L Gerez; Ana V Rodríguez (PLoS ONE)
We have demonstrated previously that a soluble factor (LrS) produced by Lactobacillus (L.) reuteri CRL 1098 modulates the inflammatory response triggered by lipopolysaccharide. In this study, the production of LrS by L. reuteri CRL 1098 was realized through two steps: i) bacterial biomass production, ii) LrS production, where the bacterial biomass was able to live but did not proliferate. Therefore, the simultaneous evaluation of the effect of different factors on the growth and LrS production was performed. Biomass production was found to be dependent mainly on culture medium, while LrS production with anti-inflammatory activity depended on culture conditions of the biomass such as pH, agitation and growth phase. The L. reuteri CRL 1098 biomass and LrS production in the optimized culture media designed for this work reduced the complete process cost by approximately 95%, respectively to laboratory scale cost.